Laboratory Study of Copper Nanoparticle Effect on Scale and Corrosion Rate in the Oil Field - Reno Pratiwi; Lestari Lestari; Muhammad Burhannudinnur; Syamsul Irham; Lukas Lukas (Journal of Earth Energy Science, Engineering, and Technology, 2021)
The occurrence of corrosion and scale on production equipment is an obstacle that often occurs in oil and gas exploration activities. Physical and chemical properties of formation water that come out with oil from production wells are the main variables causing corrosion and scale. In recent years, developing nanotechnology provides many benefits in various industrial activities. One product that is becoming widely known is Copper Nano Particles (CuNPs) which have anti-biotic, anti-microbial, and anti-fungal agents which are soluble in water and can be used to protect / coat metals (superficial conductive coatings of metal and non-ferrous metal). The use of nanoparticles in oil and gas exploration activities is still very limited. Specifically, the CuNPs material, its anti-bacterial and anti-fungal properties have never been researched on the possible use in the oil field. In this study, it was observed the influence of the presence of CuNPs in formation water on the potential for scale formation and corrosion. Formation water obtained from production wells in the Wonocolo region, Cepu, Central Java, is used as a sample to test the effect of CuNPs on the scale and corrosion trends. Observations have shown that the CuNPs content test at various concentrations did not have a significant effect on formation water for its tendency to form scales. While the corrosivity of water seems to be quite influenced by the presence of CuNPs, where the addition of nanoparticle material is optimal at 0.01 ppm which can reduce corrosion rates up to 95%.